Nanoradiopharmaceuticals Based on Alpha Emitters: Recent Developments for Medical Applications - Maydelid Trujillo-Nolasco; Enrique Morales-Avila; Pedro Cruz-Nova; Kattesh V. Katti; Blanca Ocampo-García (MDPI AG, 2021)
The application of nanotechnology in nuclear medicine offers attractive therapeutic opportunities for the treatment of various diseases, including cancer. Indeed, nanoparticles-conjugated targeted alpha-particle therapy (TAT) would be ideal for localized cell killing due to high linear energy transfer and short ranges of alpha emitters. New approaches in radiolabeling are necessary because chemical radiolabeling techniques are rendered sub-optimal due to the presence of recoil energy generated by alpha decay, which causes chemical bonds to break. This review attempts to cover, in a concise fashion, various aspects of physics, radiobiology, and production of alpha emitters, as well as highlight the main problems they present, with possible new approaches to mitigate those problems. Special emphasis is placed on the strategies proposed for managing recoil energy. We will also provide an account of the recent studies in vitro and in vivo preclinical investigations of α-particle therapy delivered by various nanosystems from different materials, including inorganic nanoparticles, liposomes, and polymersomes, and some carbon-based systems are also summarized.